2009
DOI: 10.2174/156720509788929273
|View full text |Cite
|
Sign up to set email alerts
|

Baseline MRI Predictors of Conversion from MCI to Probable AD in the ADNI Cohort

Abstract: The Alzheimer’s Disease Neuroimaging Initiative (ADNI) is a multi-center study assessing neuroimaging in diagnosis and longitudinal monitoring. Amnestic Mild Cognitive Impairment (MCI) often represents a prodromal form of dementia, conferring a 10-15% annual risk of converting to probable AD. We analyzed baseline 1.5T MRI scans in 693 participants from the ADNI cohort divided into four groups by baseline diagnosis and one year MCI to probable AD conversion status to identify neuroimaging phenotypes associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
355
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 490 publications
(387 citation statements)
references
References 88 publications
(144 reference statements)
28
355
1
3
Order By: Relevance
“…As such, mild cognitive impairment (MCI)–defined by focal memory or executive function deficits not explained by age, without dementia or loss of day‐to‐day function – has become a major focus of study 18. MCI patients convert to AD at a rate of 10–15% per year 19, 20. However, the majority of MCI patients will not transition to dementia, and some may display spontaneous improvement 19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, mild cognitive impairment (MCI)–defined by focal memory or executive function deficits not explained by age, without dementia or loss of day‐to‐day function – has become a major focus of study 18. MCI patients convert to AD at a rate of 10–15% per year 19, 20. However, the majority of MCI patients will not transition to dementia, and some may display spontaneous improvement 19.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of MCI patients will not transition to dementia, and some may display spontaneous improvement 19. Currently, estimates of hippocampal or entorhinal cortex volume coupled with cognitive function testing are the best predictors of disease transition 20, 21. However, reconstructive MRI imaging is expensive and not easily transferable to community hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely applied to the study of regional grey-matter alterations in various disorders [14][15][16][17][18][19][20][21] . The medial temporal lobe (including the hippocampus and parahippocampus) most consistently exhibits decreased grey-matter volume in AD and MCI [12,16,17,[22][23][24][25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…Diverse sets of neuropsychological tests and biomarkers have been investigated for their efficacy to predict conversion from MCI to AD [7][8][9][10][11], and several studies have shown that combining results can yield even better predictions [12][13][14]. Increased knowledge about cognitive tests and biomarkers has influenced a recent proposal for a new lexicon, where the term AD encompasses the whole spectrum of the disease from predementia to dementia phases and further emphasizes the combination of clinical and biomarker data [15].…”
Section: Introductionmentioning
confidence: 99%